Analisa Usahatani Padi Ciherang dengan Sistem Tanam Jajar Legowo di Kecamatan Sungai Pandan Kabupaten Hulu Sungai Utara - Purna Kusumayana; Norma Yunita (Rawa Sains: Jurnal Sains STIPER Amuntai, 2016)
This Research aims to determine the cost of production, receipts, revenues, profits and determine the feasibility. The research was conducted in the District of Sungai Pandan Hulu Sungai Utara Regency Province South Kalimantan. In system planting of jajar legowo, the average cost of total respondents for one-time farmer planting season in the District of Sungai Pandan is Rp 11.332.588,75,- /farming. Receipts obtained average is Rp 18.149.982,- /farming. and the average farm income is Rp 12.717.856,85,- /farming, while the average profit farm farmer respondent was Rp 6.817.393,-/farming, profits obtained by farmers every kilograms respondent was Rp 1.714, /farming. Feasibility average in rice farming of Ciherang cropping systems jajar legowo in the District of Sungai Pandan. in rice farming of Ciherang cropping systems jajar legowo. In the system of jajar legowo feasibility averages on rice farming Ciherang received by farmers is for farmers is 1,61/farming meaning that farming is worth the effort.